Efficacy and safety of Shuxuening injection in intracerebral hemorrhage: a systematic review and meta-analysis - Song, Wenting; Liu, Yaoyuan; Kang, Chaofan; Zhang, Yazi; Yan, Xing; Jin, Xinyao; Wang, Yuetong; Yang, Fengwen; Pang, Wentai (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the efficacy and safety of Shuxuening injection (SXNI) in the treatment of patients with intracerebral hemorrhage (ICH).MethodsThis study included randomized controlled trials published before 1 June 2024 in eight databases. Patients with ICH were included, with the control group receiving conventional treatment (CT) and the treatment group receiving additional SXNI on this basis. The primary outcome was neurological impairment score. The secondary outcomes were overall efficacy, cerebral hematoma volume, cerebral edema volume, activities of daily living (ADL) score, erythrocyte sedimentation rate (ESR), hematocrit (HCT), hypersensitive C-reactive protein (hs-CRP), low cut whole blood viscosity, high cut whole blood viscosity and adverse events (AE). The methodological quality of the included studies was assessed using the revised Cochrane Risk of Bias tool (ROB 2.0). For binary variables, risk ratios (RR) were calculated, while for continuous variables, mean differences (MD) or standardized mean differences (SMD) were calculated, based on 95% confidence intervals (CI).ResultsA total of 29 trials involving 3,012 participants were included. Compared with the control group, the treatment group demonstrated better performance in reducing neurological impairment score [SMD = −0.99, 95% CI −1.24, −0.73], improving overall efficacy [RR = 1.22, 95% CI 1.14, 1.30] and ADL score [SMD = 2.01, 95%CI 1.55, 2.46], as well as decreasing the cerebral hematoma volume [MD = −6.98, 95% CI −8.76, −5.20] and cerebral edema volume [MD = −3.67, 95%CI -5.27, −2.06], with statistically significant differences observed. Meanwhile, the incidence of AE in the treatment group was lower than that in the control group, with a statistically significant difference [RR = 0.63, 95%CI 0.41, 0.96].ConclusionThis study indicates that the combined use of SXNI and CT may be beneficial for the treatment of patients with cerebral hemorrhage compared to the use of CT alone. However, due to the moderate to very low certainty of evidence, it is advisable to conduct highquality clinical trials to validate the findings of this study.